A POPULATION-BASED STUDY ON MYELODYSPLASTIC SYNDROMES IN THE LAZIO REGION (ITALY), MEDICAL MISCODING AND 11-YEAR MORTALITY FOLLOW-UP: THE GRUPPO ROMANO-LAZIALE MIELODISPLASIE EXPERIENCE OF RETROSPECTIVE MULTICENTRIC REGISTRY - Flavia Mayer; Laura Faglioni; Nera Agabiti; Susanna Fenu; Francesco Buccisano; Roberto Latagliata; Roberto Ricci; Maria Antonietta Aloe Spiriti; Caterina Tatarelli; Massimo Breccia; Giuseppe Cimino; Luana Fianchi; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2017)
Results on myelodysplastic syndromes (MDS) from population-based studies are rare and these data are infrequently collected by cancer registries because diagnostic difficulties and under-reported data.